Are clinical features in Löfgren’s syndrome-related erythema nodosum different from idiopathic erythema nodosum? - Dönmez, S.; Kisacik, B.; Nuri Pamuk, et al., Ö. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background and Objectives:We retrospectively evaluated acute sarcoidosis (Löfgren’s syndrome) patients diagnosed at 2 centers and compared the clinical features of Löfgren’s syndrome (LS) related erythema nodosum (EN) to patients with idiopathic IEN who were diagnosed within the same time frame. Methods: Thirty patients (10 males, 20 females) who were diagnosed with LS and were being followed up for the last 8 years at 2 centers were included. Thirty patients (4 males, 26 females) who were admitted to the rheumatology outpatient clinics for IEN during that time period were taken as controls. The clinical and laboratory features at the initial admission, treatment modalities and response were recorded. Results: Twentyfour (80%) patients with LS related EN had arthritis and/or arthralgia. Fifteen of them had only findings of periarticular ankle inflammation and 4 had polyarthritis.When LS related EN patients were compared to IEN patients, the former group had more arthritis and/or arthralgia (p